2021
DOI: 10.1155/2021/8844104
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Echinococcosis/Hydatid Cyst Coinfection with HIV: A Report from Shiraz, Iran

Abstract: HIV coinfected with other parasitic diseases may cause a serious problem for the patients. A few case reports describing echinococcosis with human immunodeficiency virus (HIV) infection have been reported in the world; however, it has not been reported in Iran, so far. Here, the first case of liver hydatid cyst coinfected with HIV in Iran is reported. The patient is a 46-year-old female HIV-positive based on the laboratory report. Her clinical symptoms included abdominal pain, abdominal enlargement, and anorex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
2
3
0
3
Order By: Relevance
“…The most frequent symptom is abdominal pain 8 , which is almost always associated with complications due to the size of the cyst. In our case, the multicystic mass compressed multiple organs (stomach, intestines, ureters and bladder) due to its size; it also led to the appearance of symptoms such as anorexia, nausea and vomiting, similar to previous reports 8 - 12 . The patient presented stress incontinence and lower limb edema, which are considered to be rare symptoms.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The most frequent symptom is abdominal pain 8 , which is almost always associated with complications due to the size of the cyst. In our case, the multicystic mass compressed multiple organs (stomach, intestines, ureters and bladder) due to its size; it also led to the appearance of symptoms such as anorexia, nausea and vomiting, similar to previous reports 8 - 12 . The patient presented stress incontinence and lower limb edema, which are considered to be rare symptoms.…”
Section: Discussionsupporting
confidence: 89%
“…The immunity mechanisms involved in the defense against echinococcosis are characterized by the activation of Th2 cells and a Th1 subset, which leads to the expression of immunoglobulin isotypes (IgG4 and IgE) and eosinophilia 19 . In our case, transient eosinophilia was found after surgery, which could have been due to the rupture of some cysts during surgical removal 12 , considering that the hystopathological study reported the presence of viable cysts.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The vast majority of cases reported in the literature concerning infection of CE in PLWH confirms this data [ 117 , 118 , 119 , 120 , 121 , 122 , 123 ]: most of them had a full recovery after treatment. There are two cases of AE in seropositive patients [ 124 , 125 ], and a case of Echinococcus vogeli , causing polycystic echinococcosis [ 126 ].…”
Section: Echinococcosissupporting
confidence: 69%
“…Cystic echinococcosis (CE) is a common parasitic infection of humans and animals caused by the larva of 9pt?>Echinococcus granulosus sensu lato and cystic echinococcosis is a widespread zoonotic disease of global concern This disease has been reported in humans from all parts of Iran [1][2][3], and Cystic echinococcosis is considered an endemic chronic disease that is seen in many countries of the world [4]. Eurasia, Africa, Australia, and South America, obscenity is prevalent.…”
Section: Introductionmentioning
confidence: 99%